Analisis Hubungan Kebaikan Drosophila SP. dari Daerah Batu, Tulungagung dan Jombang Menggunakan Indeks Kesamaan dan Metode Dendogram - Atika Anggraini; Lidiya Fatmaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Abstrak: Drosophila sp. is a genus of organisms with a wide distribution pattern. This research aims to determine the relationship between Drosophila species in three areas, namely Batu, Tulungagung and Jombang. The research was carried out from April to June 2020 at three locations in these three regions. The samples in this study were Drosophila caught from 3 areas in the following areas: Batu, Jombang, and Tuluangung. Data was obtained from observing the morphological characteristics of captured Drosophila species originating from these three regions. The similarity analysis obtained is then carried out using a similarity index and displayed in the form of a dendogram. The final analysis displays the taxonomic dendogram findings. The results of the research show that the closest relationship between catches from the Batu area and the Tulungungung area is 0.966, which has an association coefficient value close to 1.00. This shows that there is a close relationship between species originating from the Batu and Jombang areas. Keywords: Kindness relations, Similarity Index, Dendogram Method